PENGEMBANGAN KOGNITIF ANAK MELALUI KEGIATAN MENGELOMPOKKAN BENDA DENGAN MEDIA BOLA WARNA - Riska Hapsari (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
The problem of this research is the lack of children's fine motor skills, low cognitive abilities of children, media and methods that do not vary, the activities carried out are less memorable for children, the results of the activities are not in accordance with teacher expectations. This study aims to hone children's cognitive skills through the grouping of objects with color ball media. This type of research is Classroom Action Research (CAR) using data collection techniques such as observation, documentation, and tests. The data analysis technique used in this study is a qualitative descriptive comparison and percentage, meaning that the results of observations assessing the cognitive abilities of children before giving action compared with the ability after giving action, in the form of a simple percentage, the preliminary data shows the child's ability to group objects according to size, shape, and color get a percentage value in the category enough, in the first cycle to reach the category of good value, while the second cycle gets a value with a very good category. The conclusion of the study is that children's cognitive abilities can be improved through the performance of grouping objects with color ball media in the Kampar Permata Play Group of Left Middle Kampar.